Pengembangan Media Lubang Multi Level Untuk Pembelajaran Lempar Tangkap Bola Kecil (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
This research aims to develop a media Hole Multi Level to capture the small ball throwing learning grade IV elementary school level that can increase students roll control. The model of the research is the development of research and data analysis in the form of a percentage of data types with a description of the qualitative and quantitative. Procedure development include; 1) Potential problems, 2) Data collection, 3) Early media product design Multi Level Hole, 4) Design Validation by expert penjas and learning experts, 5) Revision products I, 6) Trials I in MI Ma’arif NU Darmakradenan, 7) Product revision II, 8) Trial II at four elementary school in the village of Darmakradenan, 9) Product revision III, 10) And products. The results of expert validation against the media Pit Multi Level was 80%, I Test of 83,23%, and II trials of 85.97%. Those results can be concluded that the development of the media Pit Multi Level can be used to capture the small ball throwing learning grade IV elementary school level.